The Gospel according to Saint Luke: in Anglo-Saxon and Northumbrian versions synoptically ... - Walter Williams Skeat (At the University Press, 1874)
Book digitized by Google from the library of Oxford University and uploaded to the Internet Archive by user tpb.
Keywords: luke